2008
DOI: 10.1038/nature07427
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a prostate from a single adult stem cell

Abstract: The existence of prostate stem cells (PSCs) was first postulated from the observation that normal prostate regeneration can occur after repeated cycles of androgen deprivation and replacement in rodents. Given the critical role of PSCs in maintaining prostate tissue integrity and their potential involvement in prostate tumorigenesis, it is important to define specific markers for normal PSCs. Several cell-surface markers have been reported to identify candidate PSCs, including stem cell antigen-1 (Sca-1, also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
375
1
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 380 publications
(391 citation statements)
references
References 28 publications
13
375
1
2
Order By: Relevance
“…Bipotential cells have also been isolated based on p63 expression [139]. Remarkably, single murine prostatic cells can form complete functional acini when transplanted under the renal capsule, these cells expressing CD117, CD44, CD133 and Sca-1 [140].…”
Section: Male Gonadal and Accessory Sex Tissuementioning
confidence: 99%
“…Bipotential cells have also been isolated based on p63 expression [139]. Remarkably, single murine prostatic cells can form complete functional acini when transplanted under the renal capsule, these cells expressing CD117, CD44, CD133 and Sca-1 [140].…”
Section: Male Gonadal and Accessory Sex Tissuementioning
confidence: 99%
“…Immunostaining shows that the CD117 + (c-Kit, stem cell factor receptor) population is enriched proximal to the urethra, predominantly in the basal layer (~3% of total basal cells). Fractionated CD117 + cells combined with rat UGSM (urogenital sinus mesenchyme) and transplanted under the kidney capsules can regenerate prostate-like structures comprising cells of the basal (K14 + ), luminal (K18 + ), and, for the first time, neuroendocrine (synaptophysin + ) lineages, thereby demonstrating tripotency [17]. Single cell-reconstitution assays achieved successful engraftments in 14 of 97 single cell transplantations (along with rat UGSM).…”
Section: Dean G Tang 459mentioning
confidence: 99%
“…Again, the regenerated tubules are of clonal origin and contain both basal (e.g., K5 + , p63 + ) and luminal (K8 + ) cells providing evidence for the existence (and identity) of bipotential normal mouse prostatic basal stem cells. Further purification using the Lin -Sca-1 + CD133 + CD44 + CD117 + marker profile reveals multipotent prostate stem cells in the basal compartment [17]. Immunostaining shows that the CD117 + (c-Kit, stem cell factor receptor) population is enriched proximal to the urethra, predominantly in the basal layer (~3% of total basal cells).…”
Section: Dean G Tang 459mentioning
confidence: 99%
See 1 more Smart Citation
“…These cancer stem cells seem to be associated with the basal layer of prostate epithelium; a region reported to have high expression levels of c-KIT (Ceder et al 2017;Leong et al 2008). Moreover, it was demonstrated that tumorigenesis induced by prostate cancer stem cells is accompanied by the increased expression of c-KIT (Peng et al 2015).…”
Section: The Jak/stat Pathwaymentioning
confidence: 99%